STUDI PEMIKIRAN HADIS DI INDONESIA Analisis Teori Hadis Hasbi Ash-Shiddieqy - Hedhri Nadhiran (State of Islamic Institute Langsa, 2017)
This paper attempts to reveal the theory of Hadith of Ash- Shiddieqy, one of the reformers in Indonesia. This topic is interesting to be discussed because Hasbi has been known as an Islamic jurist so that his ideas in the field of Hadith development are almost untouchable. This phenomenon strengthens the thesis of the Federspiel – an Indonesianist, who argues that the study of hadith is particularly unpopular in Indonesia. In researching Hasbi's Hadith, the focus is directed to three crucial issues around the polemic of modern hadith discourse, which is about the limits of the notion of hadith, hujjah and the science of fiqh al-hadis. The analysis of these three topics shows Hasbi's renewal ideas in the field of Hadith, especially in the context of the Indonesian period. This at once shows his independence for his ijtihad and does not want to be bound by bigotry against a particular school of thought.